PENGARUH KOMPOSISI MEDIA TANAM DAN ZPT ATONIK TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Kisey Bina Habeahan; Hermawati Cahyaningrum; Himawan Bayu Aji (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[EFFECT OF PLANTING MEDIA COMPOSITION AND ATONIC GCS ON THE GROWTH OF COCOA SEEDS (Theobroma cacao L.)]. Cocoa (Theobroma cacao L.) is one of the essential crop commodities which is prospective and provides an excellent opportunity to improve community welfare. This study aimed to determine the effect of combination planting media and atonic growth control substances (GCS) on the growth of cocoa seedlings (Theobroma cacao L.). The research was conducted at Jalan Harmonika Baru Pasar 2, Tanjung Sari Medan in March -June 2019. The research was carried out using factorial randomized block design (RBD) with two factors: planting media (manure, ultisol soil, sand) and atonic GCS (0, 1, 2, 3 cc/L water). The first factor is the composition of the growing media in the form of manure, ultisol soil, and sand which consists of 4 fields, namely control, ratio 1:1:1, ratio 1:2:1, and ratio 1: 3:1. The second factor is the dose of atonic GCS application, which consists of 4 levels, namely without atonic GCS application, 1 cc/L, 2 cc/L water, and 3 cc/L water. The results showed that the combination of planting media consisting of manure, ultisol, and sand with a ratio of 1: 3: 1 has a significant effect on increasing plant height, stem diameter, number of leaves, and leaf area of cocoa seedlings. The atonic growth control substances of 3 cc/L water significantly increased plant height, stem diameter, number of leaves, and leaf area of cocoa seeds. The interaction between the growing media composition and the concentration of GCS atonic significantly affected the number of leaves. However, it was not significant for plant height, stem diameter, and leaf area of cocoa seeds. To conclude, the composition of the planting medium and atonic growth control substances significantly affect the growth of cocoa seedlings (Theobroma cacao L.)